2002
DOI: 10.1177/152263790200400301
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Race in Black and Whiteness: Media Coverage of Public Support for President Clinton

Abstract: This study employs a framing analysis of media explanations regarding public support for President Clinton during the 1998 coverage of the Monica Lewinsky scandal. An analysis of broadcast, newspaper, and magazine stories during the scandal reveals that media coverage of support for the President focused exclusively on African Americans. Five discursive frames were used to explain African American support: morality, political pragmatism, distrust of the criminal justice system, forgiveness/redemption, and Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Explorations of race in media studies have observed how the pervasiveness of white perspectives in the media is one of the media’s most powerful attributes (Croteau et al., 2012). The normalisation of whiteness as the taken-for-granted standard against which other racial groups are judged underpins media reporting from journalists and commentators of all racial identifications (Brooks and Rada, 2002; Croteau et al., 2012; Gabriel, 1998). Indeed, as Nakayama (2000) observes, media discourses of whiteness serve to reinforce not only a system of racial domination, but also gender, class, sexuality, location and nationality.…”
Section: Methodsmentioning
confidence: 99%
“…Explorations of race in media studies have observed how the pervasiveness of white perspectives in the media is one of the media’s most powerful attributes (Croteau et al., 2012). The normalisation of whiteness as the taken-for-granted standard against which other racial groups are judged underpins media reporting from journalists and commentators of all racial identifications (Brooks and Rada, 2002; Croteau et al., 2012; Gabriel, 1998). Indeed, as Nakayama (2000) observes, media discourses of whiteness serve to reinforce not only a system of racial domination, but also gender, class, sexuality, location and nationality.…”
Section: Methodsmentioning
confidence: 99%
“…Structuring Race, Class, and Gender Through Popular Culture Brooks and Rada (2002) argue that the media shape our ideas about race through the cultural production of meaning. Critical studies of media and popular culture have produced abundant evidence of just how social structures are reproduced through media.…”
Section: Submerged By the Culture Industriesmentioning
confidence: 99%
“…The power of whiteness lies in its nonvisibility, its appearance as universal (Nakayama & Krizek, ; Shome, ). Thus whiteness serves as a norm by which non‐Whites are measured (Brooks & Rada, ).…”
Section: Media and Minorities: Concepts And Theoriesmentioning
confidence: 99%
“…The power of whiteness lies in its nonvisibility, its appearance as universal (Nakayama & Krizek, 1995;Shome, 2000). Thus whiteness serves as a norm by which non-Whites are measured (Brooks & Rada, 2002). Brooks and Rada (2002) examined the media coverage of public support for former U.S. president Bill Clinton in 1998, when he was involved in the Lewinsky sex scandal.…”
Section: Media and Minorities: Concepts And Theoriesmentioning
confidence: 99%
See 1 more Smart Citation